Socio-cognitive factors in road safety monitoring – Cross-national comparison of driving under the influence of alcohol, drugs or medication. (October 2020) - Meesmann, Uta; Torfs, Katrien; Cools, Mario
Abstract: The objective of the study is to assess the relation between socio-cognitive factors and unsafe traffic behaviour in different national settings. The study is based on the results of the second edition of ESRA ( E -Survey of Road users' Attitudes), which was conducted in 32 countries in 2018 (ESRA2). The investigation focuses on the topic driving under the influence of alcohol, drugs, or medication (DUI) and related socio-cognitive constructs, i.e., attitudes, norms, perceived behaviour control, intention, and habits, and risk perception . Cross-national differences are assessed upon the example of Australia, Belgium, Canada, Egypt, Japan, Nigeria, and Slovenia. In the analysis, principal component analysis (PCA) was used to test the dimensions of the underlying socio-cognitive constructs and to define composite scores for further analysis. Linear regression models were fitted to investigate the association between these socio-cognitive factors and self-reported DUI. The same set of variables was used for all the linear regression models, i.e., the cross-national model (32 countries), and the seven national models. In total, 25, 459 car drivers (at least a few days a month), were included in this analysis. The results show that: ( i ) the considered socio-cognitive factors are able to predict self-reported DUI across the different countries; ( ii ) these socio-cognitive factors are also able to predict DUI on a national level; ( iii ) the impact of socio-cognitive factors on DUI differs across countries. The strongest predictor in all countries was the construct habits, followed by norms and, to a lesser extent, attitudes and intention . Perceived behaviour control and risk perception only showed a significant effect on reported DUI in a few countries. In conclusion, the ESRA2 data offer a unique opportunity to gain valuable insights into cross-national differences in traffic safety. Future research will focus on a more in- depth analysis of cross-national differences to other road safety topics. Highlights: This study assesses the relationship between socio-cognitive factors and unsafe traffic behaviour across cultural settings. The investigation focuses on driving under the influence of alcohol, drugs, and medication (DUI) using data from ESRA2. The considered socio-cognitive factors can predict self-reported DUI in different countries. Socio-cognitive factors can also predict DUI on a national level, but the impact differs across countries. The strongest predictor construct in all countries was habits, followed by norms .